Jinx, Control, and the Necessity of Adjustment: Superstitions Among Football Fans - Levental, Orr; Carmi, Udi; Lev, Assaf (Frontiers in Psychology, 2021)
Superstitions are behaviors human beings use to gain a sense of control over certain events in their lives. Thus, sport and its inherent uncertainty provide fertile ground for superstitious behavior. Research on this subject has focused mainly on athletes while examining the behavioral expressions, motivations, and characteristics of fans’ superstitions that have remained marginal; therefore, the present paper aims to address this lacuna by analyzing these behaviors as part of sports fandom and fans’ daily routines. Semi-structured interviews were carried out with 24 Israeli football fans of local teams. Key findings illustrate two themes: time dependent acts of superstition; and place. It is argued that superstitious behavior serves fans in two ways. First, making them feel their actions influence the match outcomes and helping their favorite team beyond simply cheering in the stands. Second, reducing the level of uncertainty and subsequent stress level characteristic of being a sports fan. Furthermore, following the outbreak of the COVID-19 pandemic when fans' access to stadiums was restricted, the results show that the fans’ absence from the stadiums led to a reduction in the quantity and frequency of their superstitious behaviors, pointing to the significance of sporting venues in fan behavior.